2014
DOI: 10.1177/0004867414553951
|View full text |Cite
|
Sign up to set email alerts
|

Switching suicide methods as a predictor of completed suicide in individuals with repeated self-harm: A community cohort study in northern Taiwan

Abstract: The findings in this study give us some insight into the patterns of methods in repeat suicide attempters. The intent behind switching methods of suicide attempt might be considered as an important item of clinical assessment of the seriousness of suicidal behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…Several studies have examined method-switching following self-harm [ 10 , 23 , 24 , 29 , 58 ] and a previous review found that no discernible patterns in terms of escalation to methods of potential lethality can be identified [ 23 ]. The most common pattern of method-switching reported in many studies is from self-injury, including using methods with high potential lethality (e.g., drowning, hanging and jumping) [ 25 , 26 ], to self-poisoning [ 23 ]. While the risk of method-switching and repetition is lower for IDO than other methods [ 24 ], most people who die by suicide have used the methods of IDO or cutting in their index episodes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined method-switching following self-harm [ 10 , 23 , 24 , 29 , 58 ] and a previous review found that no discernible patterns in terms of escalation to methods of potential lethality can be identified [ 23 ]. The most common pattern of method-switching reported in many studies is from self-injury, including using methods with high potential lethality (e.g., drowning, hanging and jumping) [ 25 , 26 ], to self-poisoning [ 23 ]. While the risk of method-switching and repetition is lower for IDO than other methods [ 24 ], most people who die by suicide have used the methods of IDO or cutting in their index episodes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within this study, 16% of young people who switched method after an index episode of IDO switched to attempted hanging in their next repetition episode and 9% to attempted drowning. These patterns—together with increasing trends in the use of methods with high potential lethality among young people [ 3 ]—are concerning as switching to a more lethal method in repeat self-harm is a significant predictor of suicide [ 26 ]. This and other research recommend that all young people who present to hospital following self-harm should receive a mental health assessment [ 23 , 59 ], in line with best practice guidelines [ 51 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the suicide behaviors, poisoning and cutting/piercing are regarded as low-lethal methods; but charcoal burning and poisoning by gases, hanging, and jumping from high places belong to the high-lethal methods [ 39 ]. Compared with those aged ≥65 years, patients aged between 20 and 49 years were observed to be less likely to choose a highly lethal method when attempting suicide [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Кумулятивный риск повторения аутоагрессии превышает 9% в течение первого года после индекс-эпизода и 14% в течение ближайших трех лет [10]. Переход к использованию высоколетальных способов в последующих суицидальных попытках считается очень серьезным предиктором завершенного суицида [11].…”
unclassified